3-tiered structural health monitoring framework for wind turbine blades and masts based on portable ground-based real aperture radar damage condition metrics. - Ochieng, F.X. (2019)
Metrological features like vertical gradients in wind speeds, wind direction, and turbulence intensity are becoming more decisive in design and deployment of wind turbines (WT). This has fueled a need for new measurements techniques to collect the specific parameters for structural health monitoring (SHM) of the wind mast and blades. Importantly it has led to an increase in non-contact measurement techniques as well as the need for better-validated modelling techniques that address problems of (a) flutter and (b) type and component certification of WT blades and masts. One such novel approach is the use of Ground-Based Radar (GBR) as a non-contact SHM sensor.